2019
DOI: 10.1177/1049732319874038
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Bad News Delivery Practices during Miscarriage Diagnosis

Abstract: Miscarriage is one of the most common pregnancy complications health care providers discuss with patients. Previous research suggests that women’s distress is compounded by ineffective communication with providers, who are usually not trained to deliver bad news using patient-centered dialogue. The purpose of this study was to use a patient-centered approach to examine women’s experiences with and perspectives of communication during a miscarriage to assist in the development of communication training tools fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 30 publications
0
47
0
4
Order By: Relevance
“…Intern OSCEs from the graduating classes of 2015-2018 were identified and reviewed (n = 40) [ 21 ]. OSCEs in that time frame consisted of counseling a patient on an unexpected miscarriage.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intern OSCEs from the graduating classes of 2015-2018 were identified and reviewed (n = 40) [ 21 ]. OSCEs in that time frame consisted of counseling a patient on an unexpected miscarriage.…”
Section: Methodsmentioning
confidence: 99%
“…Specific behaviors the focus group identified as important positive and negative behaviors exhibited by healthcare providers when delivering sensitive information [21].…”
Section: Table 1: Focus Group Feedback For Delivering Sensitive Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, despite the high frequency of miscarriages, studies from around the world continue to report that emergency departments (EDs) often fail to support women through the complexity of this experience by not providing the compassionate care and emotional support required during this traumatic time (Lee & Slade, 1996; MacWilliams et al, 2016). Other research has shown that these difficult experiences are compounded by ineffective communication with providers, who struggle to deliver bad news using patient-centered dialogue (Brann et al, 2020). Health care providers tend to focus on the physical aspect of miscarriage and overlook the social and psychological components of this experience, which coupled with a societal shroud of silence around miscarriage, leads to women feeling a lack of support and vulnerable to mental distress (Evans et al, 2002).…”
Section: Introductionmentioning
confidence: 99%